Intertekstualitas Legenda Nini Anteh Dan Legenda Chang’e: Komparasi Budaya Sunda Dan Tionghoa - Yostiani Noor Asmi Harini; Arief Dwinanto; Dina Srirahayu (Badan Riset dan Inovasi Nasional (BRIN), 2026)
This article seeks to examine the intertextual relationship between the Sundanese legend of Nini Anteh and the Chinese legend of Chang’e as a reflection of cultural harmony between the two societies. The research adopts a qualitative approach, using comparative textual analysis grounded in Julia Kristeva’s theory of intertextuality, alongside cultural diffusion theory to explore potential historical links shaped by migration and trade interactions between Sundanese and Chinese communities. The findings indicate that both legends are connected through the shared motif of “the woman in the moon,” creating a web of cross-cultural meanings. Nini Anteh, associated with her saepi knowledge, and Chang’e, known for her elixir of immortality, are portrayed as female figures who exercise agency over their destinies, undergo isolation as a transformative process, and reflect societal ideals of womanhood within their respective cultures. The similarity in narrative shows a symbolic resonance that reflects a shared cosmological imagination concerning the moon across different cultural traditions. In addition, the Ngabungbang tradition in Sundanese society and Zhōngqiū Jié in Chinese society represent collective respect for the full moon as a symbol of cosmic harmony. This study concludes that the intertextual connection between these two legends not only reveals shared symbolic meanings but also offers potential for their use in enhancing Intercultural Communicative Competence (ICC) through education rooted in local wisdom, ultimately promoting harmonious intercultural dialogue.